Oenanthe millefolia (Umbelliferae), a new species record for the Turkish and Greek Flora - Guner, Ebru Dogan; Teksen, Mehtap; Bani, Baris (Pensoft Publishers, 2016)
Oenanthe millefolia (Apiaceae), which is presented as a new recorded species for the Turkish flora, was discovered for the first time in Kırklareli province of Turkey. It is also reported as a new species for the Greek flora based on an unidentified specimen which was collected from the Thrace region of Greece. In this study, an expanded morphological description, the geographical distribution, the habitat properties and the ecological features of the species are exhibited with illustrative figures. Moreover, the micromorphological and anatomical characters of the fruits and the anatomical properties of the stem, petiole, leaves and the palynological features of Oenanthe millefolia are determined and described for the first time.
Keywords: Morphology; Greece; Turkey; Botany; Balkan flora; taxonomy; pollen; QK1-989; morphology; Oenanthe; Pollen; Anatomy; Bulgaria; Taxonomy; Research Article; 15. Life on land; 13. Climate action